Ten Successful Years: A Longitudinal Case Study of Autonomy, Control and Learning - Enehaug, Heidi (Nordic Journal of Working Life Studies, 2017)
The article examines three concepts closely related to the Nordic sociotechnical tradition: responsible autonomy, learning, and control. The longitudinal case study analyses the implementation of a 6-hour workday and the development of responsible autonomy, employee control, and productive organizational learning in a Norwegian factory from 2001 to 2012. The development process was successful, with productivity increasing by 20% within 1 year. We found that productivity improvements and positive work environment changes were made possible by developing responsible autonomy through an employee-driven innovation process that led to a focus on quality and productivity throughout the organization. We also found that the development of responsible autonomy prevents defensive routines from disrupting the learning and development processes in the organization. We conclude that successful organizational development depends upon building responsibility through organizational learning